Determinan yang Mempengaruhi Audit Delay dengan Ukuran Perusahaan Sebagai Moderasi - Shally Khomilah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The time span between the issuance date of the audit report and the closing date of the financial year is called the audit delay. This study aims to examine the effect of profitability, solvency, liquidity, and good corporate governance proxied by the board of commissioners and audit committee on audit delay with firm size as a moderating variable. This research was conducted at trading service and investment companies listed on the Indonesia Stock Exchange in 2015-2019. The number of samples selected by purposive sampling method is 268 samples from 56 companies for five years. The type of data used is secondary data in the form of financial statements of trading services and investment companies. The data analysis technique used is Moderated Regression Analysis. The results of the study show that profitability, solvency, board of commissioners and audit committee have an effect on audit delay, while liquidity has no effect on audit delay. Firm size moderates the effect of solvency and liquidity on audit delay. But company size cannot moderate the board of commissioners on audit delay.